Narrativity and Self: Voicing Memories of Betrayal, Anger, Loss and Silence through Performances - Kalra, Preeti (Journal of Advanced Research in English & Education, 2021)
Performance, per se, is aesthetic movement, which includes expression of behaviour, gestures, beliefs, norms and rituals circumscribing the individual and community identities. The image with which one performs becomes an integral part of one’s self, it is rather projected in one’s own image of ‘who an individual is.’ It is in this parlance , the paper intends to explore the narratives of self and analyse how the “blank spaces” are being filled by defining the “hidden narratives” of the self through performances. What one sees through the construction of this discourse is how and to what extent an individual carry different selves and identities in ‘the back room of one’s mind.’ The intention to explore the multiple selves in art through the medium of performance brings into purview the multiple narratives of self, which remains hidden under the public persona. The paper explores how performance unmasks the ‘falsity of the self’ through its well arched repetitive and restored behaviours. The work looking at the narrtives of self expression resonate two different objectives of performance. On one hand, the self-expression finds a voice in performance, on the other hand, it intends one to understand, explore and form one’s own self. Thus, performance is looked upon as the ‘reflection’ and ‘formation’ of self and identity in the paper. How to cite this article: Kalra P. Narrativity and Self: Voicing Memories of Betrayal, Anger, Loss and Silence through Performances. J Adv Res Eng & Edu 2021, 6(1): 3-7.